2017
DOI: 10.5935/1806-6690.20170022
|View full text |Cite
|
Sign up to set email alerts
|

Forage value of superior interspecific hybrids of Paspalum

Abstract: RESUMO -O objetivo deste estudo foi avaliar a expressão de caracteres agronômicos e a tolerância ao frio de híbridos apomíticos de Paspalum plicatulum x P. guenoarum, bem como estimar suas correlações fenotípicas, em duas regiões edafoclimáticas distintas. O estudo foi conduzido em diferentes locais e anos de avaliação, em delineamento de blocos ao acaso, com três repetições. Foram avaliados quatro híbridos interespecíficos de Paspalum, dois genótipos de P. guenoarum e a cv. Aruana (Panicum maximum), utilizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Inter-specific hybrids were generated in the Plicatula group of Paspalum using a chromosome-doubled sexual plant of P. plicatulum and apomictic ecotypes of different species of the Plicatula group (Novo et al, 2013; Pereira et al, 2015; Novo et al, 2016; Novo et al, 2017). New highly apomictic hybrids were generated, and several were characterized as superior for forage yield, cold tolerance, and cattle preference with respect to the apomictic male parent (Da Costa Huber et al, 2016; Motta et al, 2017; Novo et al, 2017). This approach may also be used to hybridize P. vaginatum and P. distichum , since P. vaginatum is sexual and cross-pollinated and P. distichum is mainly tetraploid and apomictic (Bashaw et al, 1970; Ortiz et al, 2013).…”
Section: Genetic Improvementmentioning
confidence: 99%
“…Inter-specific hybrids were generated in the Plicatula group of Paspalum using a chromosome-doubled sexual plant of P. plicatulum and apomictic ecotypes of different species of the Plicatula group (Novo et al, 2013; Pereira et al, 2015; Novo et al, 2016; Novo et al, 2017). New highly apomictic hybrids were generated, and several were characterized as superior for forage yield, cold tolerance, and cattle preference with respect to the apomictic male parent (Da Costa Huber et al, 2016; Motta et al, 2017; Novo et al, 2017). This approach may also be used to hybridize P. vaginatum and P. distichum , since P. vaginatum is sexual and cross-pollinated and P. distichum is mainly tetraploid and apomictic (Bashaw et al, 1970; Ortiz et al, 2013).…”
Section: Genetic Improvementmentioning
confidence: 99%
“…Because only a few trials reported the leaf:stem ratio (LSR) and harvest index (HI), we calculated these variables using the following formulae: LSR = LDMP/SDMP (PEREIRA et al, 2012;PEREIRA et al, 2015;MOTTA et al, 2017) and HI = LDMP/ TDMP (PEREIRA et al, 2012), respectively.…”
Section: Datamentioning
confidence: 99%
“…Data from six studies were used in the database: SANTOS (2005), STEINER (2005), SAWASATO (2007), TOWNSEND (2008), PEREIRA et al (2012), andMOTTA et al (2017) The studies produced 135 observations on the following species: Paspalum notatum, ecotypes André da Rocha and Bagual, and the commercial cultivar 'Pensacola'; P. guenoarum, ecotypes Azulão, Baio, and the cultivar 'Rojas'; P. urvillei: accessions collected in Rio Grande do Sul, in the municipalities of André da Rocha, Eldorado do Sul, and Bagé; P. lepton: accessions collected in Rio Grande do Sul, in the municipalities of Alegrete (26A and 26D) and Rosário do Sul (28B, 28C, and 28E); P. denticulatum and P. pauciciliatum. Two different species belonging to other genera, Panicum maximum Jacq.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…is a C 4 grass widely distributed in tropical, subtropical and temperate-warm regions. It has high nutritional value and good palatability (Robinson et al, 1988); it can be green fed, sun-dried or as silage and is suitable for grazing (Motta et al, 2017;Tejera et al, 2016;Zuloaga & Morrone, 2005).…”
mentioning
confidence: 99%